Pro PHP Refactoring - Trucchia, Francesco; Romei, Jacopo; Lowman, Michelle; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; et al. (Berkeley, CA : Apress, 2010)
Many businesses and organizations depend on older high-value PHP software that risks abandonment because it is impossible to maintain. The reasons for this may be that the software is not well designed; there is only one developer (the one who created the system) who can develop it because he didn$1 (Bt use common design patterns and documentation; or the code is procedural, not object-oriented. With this book, you$1 (Bll learn to identify problem code and refactor it to create more effective applications using test-driven design.s
Finding (3z(BBad Smells(3y (Bin Code -- to Refactoring -- Principles and Rules -- Test-First Development -- Refactoring Tools -- Structuring Behavior -- Changing Class Responsibilities -- Dealing with Data Rationalization -- Reducing to Essential Conditional Executions -- Simplifying Method Calls -- Simplifying Generalization Relationships -- Legacy Code -- Regression Tests -- Refactoring with Patterns.s
Keywords: Computer science; Software engineering; Computer Science; Computer Science, general; Software Engineering/Programming and Operating Systems